ARQ‐based updatable relay selection for distributed EO‐STBC cooperative system. (12th April 2012) - Bai, Zhiquan; Yang, Xianglai; Kwak, Kyungsup
SUMMARY In this work, we investigate the closed loop extended orthogonal‐space time block codes in decode‐ and‐forward cooperative networks and propose an updatable automatic repeat request protocol with relay selection. In the system, the relays decoding correctly are incorporated into a relay set, the optimal relays within this relay set can be selected based on the channel information, and the extended orthogonal‐space time block codes scheme is employed with the help of the feedback in automatic repeat request message. With the consideration of the relay selection, the system performance can be improved. Simulation and analysis results prove the efficiency of the proposed scheme, which achieves better performance than conventional relay schemes. Copyright © 2012 John Wiley & Sons, Ltd.